2010
DOI: 10.2109/jcersj2.118.792
|View full text |Cite
|
Sign up to set email alerts
|

Effect of B2O3 content on crack initiation under Vickers indentation test

Abstract: Effect of B 2 O 3 content on crack resistance was investigated by indentation tests of glass samples with various compositions of B 2 O 3 . The ternary SiO 2 B 2 O 3 Na 2 O glass system (SBN series) and non-alkaline aluminoborosilicate glass system (SAB series). When B 2 O 3 is substituted with SiO 2 in the SBN system ("SBN1" series), crack resistance has a relationship with density. In a series of the SBN system where density did not change with B 2 O 3 content ("SBN2" series), crack resistance decreased with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
140
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(155 citation statements)
references
References 16 publications
13
140
1
Order By: Relevance
“…However, neither E, H, and m seem to change for different cooling rates. The amount of energy dissipated by densification reduces the amount of shear taking place, which reduces the probability for cracking as a smaller amount of residual stresses is introduced and maintained in the deformed volume (Kato et al, 2010;Gross, 2012;Sellappan et al, 2013;Bruns et al, 2017). This correlation is observed for impact and quasi-static indentation testing, both showing a larger threshold load for the activation of cracks for samples that were quenched than for annealed ones.…”
Section: Resultsmentioning
confidence: 77%
“…However, neither E, H, and m seem to change for different cooling rates. The amount of energy dissipated by densification reduces the amount of shear taking place, which reduces the probability for cracking as a smaller amount of residual stresses is introduced and maintained in the deformed volume (Kato et al, 2010;Gross, 2012;Sellappan et al, 2013;Bruns et al, 2017). This correlation is observed for impact and quasi-static indentation testing, both showing a larger threshold load for the activation of cracks for samples that were quenched than for annealed ones.…”
Section: Resultsmentioning
confidence: 77%
“…Both the normal and damage-resistant glasses exhibit normal free volume and density dependence on fictive temperature (Bruckner, 1970), so the higher fictive temperature state has higher free volume and lower density. The damage-resistant glass also has approximately 7 mol% B2O3 and when added to a glass with R2O approximately equal to Al2O3, the boron exists primarily in a trigonal coordination state (Kato et al, 2010;Gross, 2017). The incorporation of trigonal units into the glass structure reduces the average coordination number of glass-forming cations and the increased ease of rearrangement of the connected, low-NBO glass network allows greater ease of densification under a sharp contact.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing a glass with many NBOs like soda-lime to a glass with few NBOs like silica, the glass with few NBOs has more free volume and this contributes greatly to its ability to densify. However, since some degree of shear aids in the densification process, the substitution of a low coordination number glass former like trigonal boron oxide in the place of tetrahedral silica has been shown to increase the crack resistance (Kato et al, 2010) despite increasing the packing density (Gross, 2017). For a glass with limited NBOs, reducing the average number of constraints on the network forming cations apparently aids in the densification process even as free volume is reduced (Gross, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is thought that the contribution of densification of glasses with a low threshold pressure does not decrease significantly with increasing load. Our previous study 19) showed that RID increases with increasing amount of 3-coordinated boron and that almost all the boron in Glass C is 3-coordinated boron. The 3-coordinated boron in Glass C may be the origin of its low threshold pressure and the small slope of its load dependence of densification.…”
Section: Aftermentioning
confidence: 92%